The Role of Islamic Banking Financing for Afforadable Housing in Realizing Sustainable Development: An Analytic Network Process (ANP) Method - Ghoni, Muhammad Abdul; Maksum, Asep (Institut Agama Islam (IAI) SEBI, 2024)
The government of the Republic of Indonesia is to provide appropriate affordable housing programs for low middle incomes. Based on the physical attributes and traditional social aspects of the low-middle income household, and social environment in the residential area, as well as their contribution to economic growth. This paper evaluates the level of prioritization of Islamic Banking Financing for affordable housing program of low-middle income families in Realizing Sustainable Development. Simultaneously, the research offers access to sustainability measurement of Islamic banking to finance affordable housing on both the social and environmental dimensions. This research utilizes An Analytic Network Process (ANP) Method to evaluate and select Sustainable Development Goal Ranking The results of this study are found that Sustainable Development Goal 8: Promote inclusive and sustainable economic growth, employment and decent work for all, is most important for Islamic banking financing for affordable housing program in Realizing sustainable Development comparing to the Sustainable Development Goals (SDGs) of goas number 9: Build resilient infrastructure, promote inclusive and sustainable industrialization and foster innovation, and Goal 11: Make cities and human settlements inclusive, safe, resilient and sustainable. Furthermore, according to the experts of Islamic Housing financing, the objective of Islamic banking financing for Affordable Housing In Realizing Sustainable Development are; to protect low-income people and people in vulnerable situations and reduce the risk for slum dwellers.